Witch queen of Redwinter - McDonald, Ed (Fantasy fiction author) (McDonald, Ed (Fantasy fiction author). Redwinter chronicles, 2024)
"Having been saved from execution at the hands of the Draoihn-powerful magic users Raine used to count as allies-Raine finds herself in the Fault, a vast magical wasteland, which is falling apart before her eyes. Alongside her two closest companions, they are searching for the only person Raine believes can help them get back home: the enigmatic and infuriatingly elusive Queen of Feathers. But what home are they trying to get back to? Ovitus LacNaithe, power-hungry traitor that he is, has taken control of the Draoihn and is unwittingly doing the bidding of a darker master. He is soon to take control of the Crown of Harranir and plunge the land into unending darkness. The fate of two worlds hangs in the balance. The stakes have never been higher. It's going to take Raine's dark, terrible powers, as well as the unbreakable bond of three friends, to ensure everyone lives to see the dawn"--